Ghana : Financial System Stability Assessment Update, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Insurance Regulation, and Securities Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The main vulnerabilities in the financial sector can be found in the banking system and the social security fund (SSNIT). The Ghanaian financial sector is also confronted by a large number of development challenges. The factual updates of Ghana's observance of the three international standards and codes illustrate the limited progress that has been achieved on the regulatory and supervisory front. IMF staff encouraged the authorities to pursue passage of the money laundering bill and seek technical assistance from the IMF to develop the essential infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet